Atrial Fibrillation Management in Acute Stroke Patients in Türkiye: Real-life Data from the NöroTek Study - Topcuoglu, Mehmet Akif; Arsava, Ethem Murat; Ozdemir, Atilla Ozcan; Aykac, Ozlem; Cetiner, Mustafa; Gencer, Elif Sarioender; Ozturk, Serefnur (Galenos Publ House, 2023)
Objective: Atrial fibrillation (AF) is the most common directly preventable cause of ischemic stroke. There is no dependable neurology-based data on the spectrum of stroke caused by AF in Turkiye. Within the scope of NoroTek-Turkiye (TR), hospital-based data on acute stroke patients with AF were collected to contribute to the creation of acute-stroke algorithms.Materials and Methods: On May 10, 2018 (World Stroke Awareness Day), 1,790 patients hospitalized at 87 neurology units in 30 health regions were prospectively evaluated. A total of 929 patients [859 acute ischemic stroke, 70 transient ischemic attack (TIA)] from this study were included in this analysis.Results: The rate of AF in patients hospitalized for ischemic stroke/TIA was 29.8%, of which 65% were known before stroke, 5% were paroxysmal, and 30% were diagnosed after hospital admission. The proportion of patients with AF who received effective treatment [international normalization ratio >= 2.0 warfarin or non-vitamin K antagonist oral anticoagulants (NOACs) at a guideline dose] was 25.3%, and, either no medication or only antiplatelet was used in 42.5% of the cases. The low dose rate was 50% in 42 patients who had a stroke while taking NOACs. Anticoagulant was prescribed to the patient at discharge at a rate of 94.6%; low molecular weight or unfractionated heparin was prescribed in 28.1%, warfarin in 32.5%, and NOACs in 31%. The dose was in the low category in 22% of the cases discharged with NOACs, and half of the cases, who received NOACs at admission, were discharged with the same drug.Conclusion: NoroTekTR revealed the high but expected frequency of AF in acute stroke in Turkiye, as well as the aspects that could be improved in the management of secondary prophylaxis. AF is found in approximately one-third of hospitalized acute stroke cases in Turkiye. Effective anticoagulant therapy was not used in three-quarters of acute stroke cases with known AF. In AF, heparin, warfarin, and NOACs are planned at a similar frequency (one-third) within the scope of stroke secondary prophylaxis, and the prescribed NOAC dose is subtherapeutic in a quarter of the cases. Non-medical and medical education appears necessary to prevent stroke caused by AF.
Türkiye’de İnme Hastalarında Atrial Fibrilasyonun Yönetimi: NöroTek Çalışması Gerçek Hayat Verileri
Keywords: Acute stroke; transient ischemic attack; anticoagulant; relapse; therapeutic dose; Holter monitoring